1999
DOI: 10.1046/j.1365-2672.1999.00499.x
|View full text |Cite
|
Sign up to set email alerts
|

Behaviour ofListeria monocytogenesunder combined chilling processes

Abstract: ) and freezing (0 and -5°C) treatments. Growth curves generated were fitted by Gompertz and Baranyi functions. The Baranyi function gave better parameter estimation values than the Gompertz equation which over-estimated the specific growth rate values. Listeria monocytogenes grew at 7°C without a lag phase, except when the sub-culture was performed at 37°C, whereas the specific growth rate was affected by the chilling processes. In fact, L. monocytogenes grew slightly faster at 7°C when a 4°C pre-incubation tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0
1

Year Published

2000
2000
2016
2016

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 72 publications
(30 citation statements)
references
References 13 publications
3
26
0
1
Order By: Relevance
“…The Gompertz model had a tendency to overestimate the rate constant (Fig. 5A), similar to growth curves in liquid (13,26).…”
Section: Resultssupporting
confidence: 59%
“…The Gompertz model had a tendency to overestimate the rate constant (Fig. 5A), similar to growth curves in liquid (13,26).…”
Section: Resultssupporting
confidence: 59%
“…These contradictory results could be due to the fact that the reference studies (1,48) were conducted using laboratory media and pure cultures. The high preincubation temperature (25 or 30°C) of the bacterial cultures used in such studies, as well as the structure and composition of the growth medium may influence the behavior of microorganisms after a shift to low temperature (10,13,30). Indeed, temperature shifts close to 0°C did not cause any significant additional lag in the growth of endogenous bacteria on other real food products (32,43).…”
Section: Resultsmentioning
confidence: 99%
“…It needs to be noted, however, that both of these studies were conducted in liquid media under laboratory conditions. It has been shown that factors such as the preincubation temperature of the bacterial culture, as well as the structure and composition of the growth medium may play an important role on the bacterial behavior after a shift to low temperature (10,13,30,45). Thus, studies with naturally contaminated actual foods would lead to the accumulation of more reliable information about microbial growth at fluctuating temperature.…”
mentioning
confidence: 99%
“…monocytogenes has been reported to grow at temperatures less than 0°C in laboratory media broth (e.g., see references 1 and 46) and in vacuum-packed foods (e.g., see references 3 and 19). However, other reported minimum growth temperatures for L. monocytogenes range from 0.5 to 5.0°C in various broth media (11,16,21,47) and from 3 to 4°C in foods (27,36,45). The model describes accurately the data used to generate it, which are mostly in the range of 4 to 30°C (see Fig.…”
Section: Model Performance Goodness Of Fitmentioning
confidence: 99%